PENYIDIKAN TINDAK PIDANA PENGGELAPAN BARANG JAMINAN FIDUSIA DI WILAYAH HUKUM POLRESTA PEKANBARU - Ilham Yudha Kurniawan; Maryati Bachtiar; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The crime of embezzlement of fiduciary collateral often occurs inIndonesia, especially the city of Pekanbaru. Meanwhile, fiduciary guarantees as aform of engagement regulated in Law Number 42 of 1999 concerning FiduciaryGuarantees are routine activities in lending transactions because the loadingprocess is considered simple, easy and fast. Fiduciary is the transfer of ownershiprights to an object on the basis of trust provided that the object whose ownershiprights are transferred remains in the control of the owner of the object. The rise ofembezzlement crimes against fiduciary guarantees cannot be separated from therole of law enforcement, including at the level of the investigation process. Themain problem in this study is the lack of security for creditors who pledge theirvaluables to debtors. In this study, the authors wanted to know how theinvestigation process was carried out by the Pekanbaru Police and wanted to findout what obstacles occurred in the investigation process against the crime ofembezzlement of fiduciary guarantees in the city of Pekanbaru.This type of research can be classified in the type of Sociological researchbecause in this study the author directly conducts research at the location orplace under study in order to provide a complete and clear picture of the problembeing studied. This research is sourced from primary data, secondary data andtertiary data, while the population and sample are the Pekanbaru Policeinvestigators who handle cases of embezzlement of fiduciary guarantees in thePekanbaru Police jurisdiction.The results of the study indicate that in terms of the investigation process,it turns out that the Pekanbaru Police are not optimal in carrying out lawenforcement as evidenced by the 20 cases that have been submitted from 2018 to2022, only 5 cases have been sentenced to court while 15 cases have beeninvestigated, this is due to the investigation process. What is done tends to chargethe reporter to prove his report without any effort or the role of law enforcementis passive while in criminal law the investigator has the authority to activelyprove a criminal act.Keywords: Crime – Embezzlement – Fiduciary